(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Organization of the system of continuous professional development of teaching staff is the urgent task of today, and the reforms implemented in the field of education are expanding more than ever. In this article, the author of the pedagogic staff, in order to increase the attention to the issue of education through the continuous professional development of the pedagogues, should increase the demands on themselves, and for this, they should work tirelessly on themselves, only then will they have a positive effect on the students. It was discussed that they can achieve results, and the expected result will be positive.